Terrestrial pollution in the Pechora basin, north-eastern European Russia - Walker, Tony Robert (2003)
The chemical composition of snow, terricolous lichens and top-soil along with abundance and diversity of lichen communities were assessed in the Pechora and Usa basins, North-Eastern European Russia. Transects were established through the principal industrial towns of Vorkuta, Inta and Usinsk to assess the spatial extent of acid or alkaline and metal deposition. A further eight sites were selected to assess local impacts of oil and gas operations.